THE USE OF WHISPERING TEAM TO ENHANCE STUDENTS’ LISTENING SKILL AT GRADE 6th OF KLASAMAN 2 ELEMENTARY SCHOOL SORONG CITY - Lulu Jola Uktolseja; Melda Agnes Manuhutu (Getsempena English Education Journal, 2018)
The aim of this journal is to enhance students’ listening skill especially the students of grade 6thof Klasaman 2 Elementary School, Sorong City, West Papua Province. The model of the research is Classroom Action Research (CAR). The researcher used test in cycles and observation sheet to due the data. The result of the data is 61% students succeed to execute the exercises in second cycle. Meanwhile, the students need more thing to help the students for example picture. The picture helped the students to remind the sentences they heard from the latest whispering person. The mean of scores in cycle 1 is 56.25 from 100 and cycle 2 is 87.5 from 100. Moreover, the students also learn character value by this game, they learnt to give appreciation for their friends whether they were succeed or failed. This game helped students to learn happily and fun.It can be proven by the observation sheet.The result and discussion of this study revealed that the implementation of whispering team game enhances students’ listening skill.The conclusion of this study revealed that the implementation of whispering team game enhances students’ listening skill.